2010
DOI: 10.1029/2009jf001606
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of the Chamousset rock column (Western Alps, France)

Abstract: [1] This paper investigates the variation of the first resonance frequency of the Chamousset limestone column (21,000 m 3 , Vercors, French Alps) before its collapse in November 2007. The site was instrumented with seismometers and extensometers during a 4-month period with some gaps in the measurements. Experimental results and numerical modeling showed that the resonance frequency of a prone-to-fall column can be derived from the spectra of continuous seismic noise records. At the Chamousset site, the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
108
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(129 citation statements)
references
References 42 publications
13
108
2
6
Order By: Relevance
“…Levy et al (2011) observed on a rock column in the French Alps that the largest numbers of events fit with minima in the temperature curve, after severe temperature drops. This result suggests a temperature control on rupture events and fracturing, what is supported by resonance frequency analysis (Levy et al, 2010). …”
Section: Seismic Monitoring Of Signals Related To Mass Movementssupporting
confidence: 56%
“…Levy et al (2011) observed on a rock column in the French Alps that the largest numbers of events fit with minima in the temperature curve, after severe temperature drops. This result suggests a temperature control on rupture events and fracturing, what is supported by resonance frequency analysis (Levy et al, 2010). …”
Section: Seismic Monitoring Of Signals Related To Mass Movementssupporting
confidence: 56%
“…At the Chamousset rock column, the source mechanism is retrieved by the P -and S-waves amplitude ratio (Lévy et al, 2010). Shear events are found to be located at the bottom of the column while tensile opening is occurring in the upper part (Lévy et al, 2010). To the best of our knowledge, for soft-rock landslides, no source mechanism was modeled.…”
Section: Discussionmentioning
confidence: 99%
“…Simple slopequakes 5 are currently assumed to be generated by shear movement along a plane or tensile opening of cracks (Spillmann et al, 2007;Helmstetter and Garambois, 2010;Gomberg et al, 2011). At the Chamousset rock column, the source mechanism is retrieved by the P -and S-waves amplitude ratio (Lévy et al, 2010). Shear events are found to be located at the bottom of the column while tensile opening is occurring in the upper part (Lévy et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations